2017
DOI: 10.12681/jhvms.14861
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Coxiella burnetii antibodies in bulk milk and blood serum and associations with reproductive indices in cow dairy herds of Central and Northern Greece

Abstract: For the first time in Greece, we investigated the prevalence of Coxiella burnetii antibodies in milk and sera from dairy cattle herds located at central and northern parts of the country. Eighty herds were initially voluntary enrolled in the study and a bulk milk sample from each farm was assayed by ELISA for C burnetii antibodies. According to antibody titre, herds were classified into 5 categories: negative and grades 1,2,3 and 4 (ascending scale). To assess the prevalence within farms, two herds from each c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Despite the aforementioned importance of C. burnetii, there is a lack of studies concerning infection with this pathogen in animals in Greece. There are a couple of serological studies in sheep and goats [19,20] and one serological study in dairy cows [21]. Molecular characterization of strains was approached in a single recent work, which examined aborted sheep fetuses [22].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the aforementioned importance of C. burnetii, there is a lack of studies concerning infection with this pathogen in animals in Greece. There are a couple of serological studies in sheep and goats [19,20] and one serological study in dairy cows [21]. Molecular characterization of strains was approached in a single recent work, which examined aborted sheep fetuses [22].…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that, in this case, C. burnetii was not a major aetiology of puerperal metritis. A study in Greece [46] also found no association between the presence of C. burnetii antibodies and uterine infection. Turcotte and colleagues [81] conducted a study about 5 weeks after calving to estimate the prevalence of C. burnetii in dairy cows from PCR-positive and/or seropositive herds.…”
Section: Metritis and Endometritismentioning
confidence: 91%
“…Similarly, in a small study involving 43 dairy cows, Garcia-Ispierto and colleagues [80] found that seropositive cows were no more likely to have an RFM than seronegative cows. Furthermore, a large study in Greece [46] grouped herds according to BTM antibody titre to C. burnetii. One-third of herds were deemed positive, and two herds per each of five herd groups (including a control group) were selected for further serum antibody titre assessments.…”
Section: Retained Placenta/foetal Membranes (Rfms)mentioning
confidence: 99%
See 1 more Smart Citation